Diagnosis of multinutrients deficiency in rainfed semi-arid tropical soils of Karnataka - LALITHA, M.; HEGDE, RAJENDRA; KOYAL, ARTI; PARVATHY, S.; NIRANJANA, K. V.; DHANORKAR, B. P.; DHARUMARAJAN, S.; SRINIVAS, S.; REDDY, R. S.; CHANDRAN, P. (Journal of Soil and Water Conservation, 2020)
Sustainability of Indian agriculture is an increasing concern because of deterioration of soil fertility particularly in rainfed areas where fertility and water constraints are the limiting factors of crop productivity. The integrated watershed management program called SUJALA by watershed department, Karnataka facilitated to diagnose the soil nutrient status in rainfed areas of Karnataka by collecting soil samples at grid interval from farmerâ€™s field. A total of 34011 geo-referenced composite soil samples (0-15 cm) were collected at 320Ã—320 m grid interval to analyze the fertility status of soils of Bidar, Chamarajanagar, Gulbarga, Gadag, Koppal, Tumkur and Yadgir districts of Karnataka. Based on the soil test values of organic carbon, available P and K, soil samples were grouped under three categories viz., low, medium and high. The results revealed that most of the samples were low in soil available phosphorus, medium to high in potassium and medium in soil organic carbon. In addition, widespread deficiency of Sulphur (S), Boron (B) and Zinc (Zn) were noticed in many places. Apart from water shortage, crops grown in rainfed semi-arid tropical soils of Karnataka suffer from multinutrients deficiencies. Hence site-specific nutrient management based on crop requirement is necessary to sustain the crop productivity in rainfed areas.